Linear and Nonlinear Aging of Lithium-Ion Cells Investigated by Electrochemical Analysis and In-Situ Neutron Diffraction. Issue 16 (22nd November 2019) - Keil, Jonas; Paul, Neelima; Baran, Volodymyr; Keil, Peter; Gilles, Ralph; Jossen, Andreas
Abstract : In this paper, we present an aging study of commercial 18650-type C/LiNi0.33 Mn0.33 Co0.33 O2 lithium-ion cells. The test procedure comprises varying charging currents, discharging currents and resting times between cycles. The cells show a nonlinear capacity fade after a few hundred equivalent full cycles, if cycled with a standard charging and discharging rate of almost 1C, and different resting times. By increasing the discharging current or decreasing the charging current, the lifetime improves and results in a linear capacity fade. The neutron diffraction experiment reveals a loss of lithium inventory as the dominant aging mechanism for both linearly- and nonlinearly-aged cells. Other aging mechanisms such as the structural degradation of anode or cathode active materials, or the deactivation of active materials, cannot be confirmed. With ongoing aging, we observe an increasing capacity loss in the edge area of the electrodes. Whereas the growth of the solid electrolyte interphase defines the early stage, linear aging, marginal lithium deposition is supposed to cause the later stage, nonlinear aging. Capacity recovery caused by lithium stripping and chemical intercalation is shown to be dependent on the cell's state of health.